(untitled) (Pädagogische Horizonte, 2017)
The present article, provocatively called ‘Some Food for Thought’, revolves around some very common misconceptions and ill-founded teaching beliefs that have come to pervade L2 teaching approaches and styles across the board. Based on the fact that the mechanisms and principles at work in both L1 and L2 acquisition are for a large part the same (compare morpheme studies, creative construction, overgeneralisation, simplification strategies etc.), the article aims to show beyond reasonable doubt that the academic style, also called the ‘grammar translation method’ or ‘get it right from the beginning’ by some, is totally counterproductive and detrimental to the learners’ confidence, especially when it comes to developing their speaking skills and fluency.